Manejo oportuno y preventivo en las úlceras por presión en pacientes de la unidad de cuidados intensivos - Olivo Guamán, Emma Cecilia (2025)
Pressure ulcers represent a high morbidity rate in intensive care services, especially in elderly patients and particularly during the stay of intubated patients. Nursing care protocols were established to reduce the incidence and risk levels through assessment scales, allowing the development of various preventive strategies and rapid actions to optimize the quality of nursing care and resources. Therefore, the objective of this article is to identify nursing care practices for the timely and preventive management of pressure ulcers in patients in the intensive care unit. A predominantly qualitative approach was applied to the research, including scientific articles indexed in databases such as PubMed, Scielo, Dialnet, and Google Scholar. Articles from non-indexed journals and undergraduate theses were excluded from the review process. As a result, the research highlighted the importance for nursing staff to know the timing of position changes, skin hygiene, and the importance of applying polyurethane gels. The bibliographic review concluded that nursing staff must work with an individualized care plan to improve the care of bedridden patients in intensive care to prevent complications such as pressure ulcers.